Est insolitum inquirere taliter : Latin and German documents from Heinricus Institoris's witch hunts in Ravensburg and Innsbruck - Mackay, Christopher S., 1962- (Studies in Central European histories, 2021)
"This is the companion volume to the author's "An Unusual Inquisition": Translated Documents from Heinricus Institoris's Witch Hunts in Ravensburg and Innsbruck (Brill, 2020), and contains a full edition of the Latin and German documents illustrating Heinricus Institoris's activities as prosecutor of witchcraft in Ravensburg in 1484 and Innsbruck in 1485. These events had a great influence on Institoris's composition of the Malleus Maleficarum, the most famous and influential early-modern textbook on witchcraft. This is the only full and complete edition of these documents, some of which have not previously been published in their entirety, and the texts greatly illuminate the historical setting of the composition of one of history's most notorious books"--